On-demand Misbehavior Detection for Vehicular Ad Hoc Network. (October 2016) - Ho, Yao-Hua; Lin, Chun-Han; Chen, Ling-Jyh
Maintaining communication links of an established communication path that extends between source and destination nodes is a significant challenge in Vehicular Ad Hoc Networks due to movement of the vehicles. Operations of Vehicular Ad Hoc Network rely on the collaboration of participating nodes to route data for each other. A critical requirement on the nodes is to cooperate with each other for successful data transmission. Thus, the impact of malicious and selfish users must be detected to ensure the operations of Vehicular Ad Hoc Network. In this article, we proposed On-demand Misbehavior Detection technique for vehicle-to-vehicle communication. We adapt two location-based routing protocols, Contention-Based Forwarding and Connectionless Approach for Streets, to our On-demand Misbehavior Detection. Various experiments are conducted to show the effectiveness and efficiency of the proposed On-demand Misbehavior Detection technique. The simulation and analytical results showed that the proposed technique is very effective in detecting misbehaving nodes.